2016
DOI: 10.3389/fmicb.2016.00379
|View full text |Cite
|
Sign up to set email alerts
|

Response to Gaseous NO2 Air Pollutant of P. fluorescens Airborne Strain MFAF76a and Clinical Strain MFN1032

Abstract: Human exposure to nitrogen dioxide (NO2), an air pollutant of increasing interest in biology, results in several toxic effects to human health and also to the air microbiota. The aim of this study was to investigate the bacterial response to gaseous NO2. Two Pseudomonas fluorescens strains, namely the airborne strain MFAF76a and the clinical strain MFN1032 were exposed to 0.1, 5, or 45 ppm concentrations of NO2, and their effects on bacteria were evaluated in terms of motility, biofilm formation, antibiotic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 72 publications
(92 reference statements)
0
11
1
Order By: Relevance
“…In P. fluorescens , no difference of swimming, swarming or twitching motility was observed with gNO 2 80 ppm, although a response delay was also noted, as previously for enzymatic activities. A different result was reported in a previous study in which 45 ppm gNO 2 were sufficient to reduce the motility of airborne and clinical strains of P. fluorescens ( Kondakova et al, 2016 ). However, it is essential to remember that P. fluorescens is a species-complex particularly wide and heterogeneous phylogenetically and physiologically and this diversity appears closely related to ecological niches ( Bodilis et al, 2004 ; Scales et al, 2014 ).…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…In P. fluorescens , no difference of swimming, swarming or twitching motility was observed with gNO 2 80 ppm, although a response delay was also noted, as previously for enzymatic activities. A different result was reported in a previous study in which 45 ppm gNO 2 were sufficient to reduce the motility of airborne and clinical strains of P. fluorescens ( Kondakova et al, 2016 ). However, it is essential to remember that P. fluorescens is a species-complex particularly wide and heterogeneous phylogenetically and physiologically and this diversity appears closely related to ecological niches ( Bodilis et al, 2004 ; Scales et al, 2014 ).…”
Section: Discussioncontrasting
confidence: 75%
“…In this strain, the biofilm roughness was markedly increased suggesting a disorganization of the matrix. The effects of gNO 2 on cutaneous P. fluorescens and C. tuberculostearicum biofilm formation were limited in contrast to those observed in airborne P. fluorescens which exhibited a high increase in biofilm thickness ( Kondakova et al, 2016 ). Globally, the impact of gNO 2 on exo-enzymes production, motility, and biofilm formation suggests that gNO 2 should have limited influence on the initial steps of cutaneous bacteria implantation on skin.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…More recently, an antibiotic resistance modulation was promoted by a bacterial NO 2 gaseous exposure. Indeed, an upregulation in expression of MexEF-OprN efflux pump was observed coupled with an increase in related antibiotic resistance [84]. The link between NO 2 and this efflux pump is yet not established, but the authors suggest here a potential role of this protein in the releasing of NOx outside the cells.…”
Section: Nox At the Center Of Prokaryotic Life Virulence And Deathmentioning
confidence: 94%
“…They also reported that the higher NO doses are used, the faster is the formation rate of NO 2 . In contrast, a direct gaseous NO 2 exposure could also be benefit in the struggle against undesirable microorganism because it seems to impact their metabolism, social behavior, and growth [84]. Moreover, a continuous high-dose NO 2 exposure seems to lead in membrane alteration through an increased permeability [98].…”
Section: The Novel Therapeutic Strategies Mediated By Noxmentioning
confidence: 99%